Explore a diverse range of topics and get expert answers on IDNLearn.com. Ask your questions and receive accurate, in-depth answers from our knowledgeable community members.

Simplify [tex]-5-\sqrt{-44}[/tex].

A. [tex]-5-4 \sqrt{11i}[/tex]
B. [tex]-5-4i \sqrt{11}[/tex]
C. [tex]-5-2i \sqrt{11}[/tex]
D. [tex]-5-2 \sqrt{11i}[/tex]


Sagot :

To simplify the expression [tex]\(-5 - \sqrt{-44}\)[/tex], we need to handle the square root of the negative number. Recall that the square root of a negative number involves imaginary numbers. Specifically,

[tex]\[ \sqrt{-a} = i\sqrt{a} \][/tex]

where [tex]\(i\)[/tex] is the imaginary unit with [tex]\(i^2 = -1\)[/tex].

Let's start by simplifying [tex]\(\sqrt{-44}\)[/tex].

[tex]\[ \sqrt{-44} = \sqrt{-1 \cdot 44} = \sqrt{-1} \cdot \sqrt{44} = i \cdot \sqrt{44} \][/tex]

Next, we simplify [tex]\(\sqrt{44}\)[/tex]. Since 44 can be factorized as [tex]\(4 \cdot 11\)[/tex], we get:

[tex]\[ \sqrt{44} = \sqrt{4 \cdot 11} = \sqrt{4} \cdot \sqrt{11} = 2 \cdot \sqrt{11} \][/tex]

Putting it all together, we have:

[tex]\[ \sqrt{-44} = i \cdot \sqrt{44} = i \cdot (2\sqrt{11}) = 2i\sqrt{11} \][/tex]

Now, substitute this back into our original expression:

[tex]\[ -5 - \sqrt{-44} = -5 - 2i\sqrt{11} \][/tex]

Thus, the simplified form of [tex]\(-5 - \sqrt{-44}\)[/tex] is:

[tex]\[ -5 - 2i\sqrt{11} \][/tex]

Therefore, the correct answer is:

[tex]\[ \boxed{-5 - 2i\sqrt{11}} \][/tex]